Echocardiographic Assessment of the Effect of Aging on the Diastolic and Systolic Functions of the Left Ventricle - Matsumoto, Masayuki; Matsumoto, Mikio; Munehira, Junichi; Tsuchiya, Hiroshi; Sekimoto, Hiroshi; Lin, Kuang-yi; Takizawa, Satoshi; Goriya, Yoshikazu; Nakatani, Akio (Nihon Rōnen Igakkai zasshi, 1991)
The effects of aging on the diastolic and systolic functions of the left ventricle were studied by echocardiography as follows. (1). Maximum velocity of circumferential fiber lengthening (negative peak Vcf) and shortening (peak Vcf) was assessed by digital M-mode echocardiography in 20 healthy young subjects and 26 healthy elderly subjects. The mean value of negative peak Vcf (-circ/sec) was -3.87±0.85 in the 20's. -4.48±1.14 in the 30's, -3.71±1.21 in the 40's, -2.70±0.90 in the 60's, -2.57±0.64 in the 70's, -2.33±0.77 in the 80's and -2.57±0.65 in the 90's showing significant difference among young and elderly groups (p<0.05-p<0.005). The mean value of peak Vcf showed no significant difference among young and elderly groups except for the group in the 30's which showed significant (p<0.05) difference between other groups. (2). Indices of the left ventricular systolic and diastolic functions were calculated by standard M-mode echocardiographic technique in 227 healthy subjects from 5 to 94 years in age by dividing them into 3 young groups and 4 elderly groups. As for the left ventricular internal diameters a tendency of increase was observed in the enddiastolic diameter of the left ventricle in accordance with ageing. Fractional shortening of the left ventricular diameter which ranged from 36.2% to 36.7% in the 3 young groups and 36.9 to 40.3% in the 4 elderly groups and cardiac output showed no age dependent decrease. The E-F slope of the mitral valve showed marked age-dependent decrease, i.e. 93.6mm/sec-108.7mm/sec in the 3 young groups and 39.5-30.7mm/sec in the 4 elderly groups. Current data distinguished the age dependent deterioration of the diastolic function from the preserved systolic function of the left ventricle. This fact seemed attributable to the increased stiffness of the left ventricular wall.